Pendampingan Pengemasan Produk Wisata Budaya “Merti Desa” Doplang - Aurilia Triani Aryaningtyas; C Susmono Widagdo; Renny Aprilliyani (Jurnal Pengabdian kepada Masyarakat Nusantara, 2022)
Doplang Village has a variety of unique traditions that have great potential to be presented as a tourist spot, one of which is the "Merti Desa" tradition. The problem that arises is that this potential has not been utilized and developed optimally because the community has not been able to package it properly. This service aims to provide support to the community to help package the village merti ceremony into a cultural tourism product that can be sold to tourists. Implementation methods include: FGD problems and assistance in packaging tourism products. The result of these activities is the preparation of village cultural event plans that are packaged in such a way that they can become tourism products offered to tourists. The activity partners have also been able to prove their readiness and success in packaging “merti desa” into extraordinary attractive product.